An Analysis of the Abstracts of EFL Undergraduate Students: Coherence and Cohesion - Widhiyanto Widhiyanto; Nurmala Hendrawaty; Lilis Suryani; Mochamad Rizqi Adhi Pratama (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Coherence and cohesion play crucial roles in writing an abstract of an undergraduate thesis. By ensuring the coherence and cohesion of the abstract, EFL undergraduate students can enhance its readability, can facilitate the understanding of the research content, and can enable readers to grasp the main points efficiently. However, EFL undergraduate students often need help achieving coherence and cohesion due to their limitations in understanding and practicing academic writing. The research aims to analyze how the sentences in the abstract are related to one another through logical connections and to identify the cohesive devices like conjunction, reference, substitution, or ellipsis to make the abstract coherent. Three abstracts were chosen randomly from 2020 to 2022. Then, the researchers analyzed the data qualitatively in words or sentences using document analysis. The results show that two out of three abstracts are coherent. It is highly suggested for EFL undergraduates whose abstracts must be more readable to improve cohesive devices and use different conjunction and adverbial sentences. Therefore, the suggestion is that EFL undergraduate students use other transitions to link each sentence to make coherent text.